COMPUTER-BASED LITERACY AND NUMERATION TRAINING FOR LEARNING CITIZENS AT THE CENTER FOR COMMUNITY LEARNING ACTIVITIES PKBM BINA WARGA MEKARJAYA - Emas Marlina; Diana Silaswati, R. Rinayanti Laila Nurwulan, Wintarsih (Adiba Aisha Amira, 2023)
The Community Learning Activity Center Community in PKBM Bina Warga Mekarjaya Development is a non-formal institution that organizes equivalency package activities in Bandung, Indonesia, which has run a computer-based national assessment test with computer-based literacy and numeracy competencies being tested, thus inviting partners to help guide and provide training for students to have these skills. Based on these needs, the community service team of Bale Bandung University, in accordance with the agreement with the management of PKBM Bina Warga Mekarjaya , carried out this service in the form of literacy and numeracy training for students at PKBM Bina Warga Mekarjaya ahead of the implementation of the computer-based national assessment test.